2022
DOI: 10.3390/biomedicines10010097
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody to GNAS in Early Detection of Hepatocellular Carcinoma: A Large-Scale Sample Study Combined with Verification in Serial Sera from HCC Patients

Abstract: The aim of this study was to explore the value of autoantibody to GNAS in the early detection of hepatocellular carcinoma (HCC). In a large-scale sample set of 912 participants (228 cases in each of HCC, liver cirrhosis (LC), chronic hepatitis B (CHB), and normal controls (NCs) groups), autoantibody to GNAS was detected with a positive result in 47.8% of HCC patients, which was significantly higher than that in patients with LC (35.1%), CHB (19.7%), and NCs (19.7%). Further analysis showed that the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…By evaluating the changes of these three autoantibodies in the clinical follow-up sera of HCC patients before and after diagnosis, it was found that the levels of these three autoantibodies were already elevated in sera collected nine, six, and three months before being diagnosed with HCC. Our findings are supported by studies on biomarkers for HCC and gastric cancer, which also revealed that autoantibodies existed in pre-malignant lesions [ 31 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 86%
“…By evaluating the changes of these three autoantibodies in the clinical follow-up sera of HCC patients before and after diagnosis, it was found that the levels of these three autoantibodies were already elevated in sera collected nine, six, and three months before being diagnosed with HCC. Our findings are supported by studies on biomarkers for HCC and gastric cancer, which also revealed that autoantibodies existed in pre-malignant lesions [ 31 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 86%
“…Tumor-associated autoantibodies (TAAbs), which are produced by cancer patients in response to tumor-associated antigens (TAAs), have emerged as promising biomarkers for early cancer detection. The immune system is an essential indicator of early tumorigenesis and progression ; thus, abnormal TAAs can be theoretically sensed by our immune system, triggering the production of TAAbs at relatively earlier stages. Various TAAbs derived from the serum and plasma of cancer patients have been utilized for the detection of different types of cancer. In HCC studies, numerous TAAbs with promising performance have been identified. Interestingly, a stepwise increase in autoantibodies has been observed during the transition from chronic liver disease to HCC, , consistent with findings in HCC mouse models, suggesting that these autoantibodies may play a significant role in HCC development.…”
Section: Introductionmentioning
confidence: 61%